Prevalence of cardiovascular risk factors and diseases in patients with osteoarthritis of knee attending orthopaedic out-patient department of a tertiary care hospital - Shah, Kunal Ajitkumar; Mohapatra, Anuradha; Velhal, Gajanan D. (International Journal Of Community Medicine And Public Health, 2019)
Background: Osteoarthritis (OA) and cardio-vascular diseases (CVD) share similar risk factors. Since OA may increase the risk of CVD through several mechanisms, this study was taken up to find the prevalence of cardiovascular risk factors and diseases in patients with OA knee. We also assessed the relationship between cardiovascular risk factors and the socio-demographic characteristics of the participants. Methods: This cross-sectional study was conducted during August 2018 to January 2019 in an Orthopaedic Out-patient Department of a tertiary care hospital in a metropolitan city. Sample size was 384. Patients above the age of 45 years who were radiologically diagnosed to be OA knee grade 2 and above were included. Questionnaire was used to collect data. Lipid profile and blood sugar were done. Perceived stress scale-10 was used for calculating stress level. Results: Physical inactivity was the most prevalent risk factor (79.68%) followed by tobacco consumption (69.27%), obesity (64.84%), unhealthy diet (56.77%), positive family history (48.43%), dyslipidaemia (48.17%), diabetes (38.54%), hypertension (27.60%), smoking, mental stress and excessive alcohol intake. Prevalence of CVDs like heart failure, heart attack, stroke and other cerebral atherosclerotic conditions were 5.98%. Prevalence among male and female was 6.16% and 5.88% respectively. Conclusions: Risk factors for cardiovascular diseases are common in patients of Osteoarthritis Knee. Physical inactivity is the most common risk factor followed by tobacco consumption, obesity and unhealthy diet. Prevalence of CVDs were 5.98%.